Proximal pulmonary artery embolization for recurrent hemoptysis after bronchial artery embolization. Issue 5 (3rd September 2021) - Swanson, Eric M.; Dickey, Brandon; Murray, James; Ruiz, Steven
Abstract: Proximal pulmonary artery (PA) embolization is a dramatic interventional radiology procedure performed to control recurrent, life-threatening hemoptysis. Distal PA embolization procedures are commonly performed, and preoperative proximal PA embolization procedures have been reported, but to the best of our knowledge there has not been a reported case of a proximal PA embolization to treat hemoptysis. Here, we present a case of a complete proximal PA embolization that effectively resolved recurrent hemoptysis in a patient with a lung tumor following a failed bronchial artery embolization.